Long-Term Firm Growth and Ownership Organization - A Study of Business Histories - Jan Glete (The Research Institute of Industrial Economics (IUI), 1989)
This paper is concerned with ownership organization in the process of industrial growth and transformation. It stresses the difficulties of changing an established and successful pattern of behavior. The meso-level of organization is used to interpret coordination of economic activities between micro-units. The importance of investigating if technological development is induced from the demand or supply side is stressed. The Swedish financial market for ownership and control and two major Swedish industrial branches: the forest industry and the engineering industry are analyzed. The slow development of an efficiency control function on the Swedish stock market is discussed.
Keywords: L22; L73; O33; 330; Firm structure; ownership; industrial growth; technological progress